Zno Based Extended Gate Field Effect Transistor (EGFET) Dosimeter Fabrication With Dopant Elements Of Pb, Al And Bi For X-Ray In Diagnostic Energy Range - Ahmed Ali, Amal Mohamed (2022)
Real time dosimetry is a major challenge in medical, industrial and education fields. One promising candidate for dosimetry is the metal oxide semiconductor fieldeffect transistor (MOSFET) dosimeter. A new design of the MOSFET dosimeter is being developed in a different study to measure the dose delivered to the tissue layers. This thesis will discuss the development of a new type of radiation detector based on the characteristics of different metal oxide materials, and a new model of radiation detector, known as extended gate field-effect transistor (EGFET) and the optimization of the operating conditions.